Miʿyār al-ashʿār wa-Mizān al-afkār fī sharḥ Miʿyār al-ashʿār - Ṭūsī, Naṣīr al-Dīn, (Miras Maktoob, ISBN: 9789004365452., 2019)
Naṣīr al-Dīn Ṭūsī (d. 672/1274) was an influential philosopher, theologian, mathematician and astronomer, besides being the first director of the famous observatory at Marāghah near Tabriz as well as a man of politics. Author of a large number of scholarly works, he is especially famous for such treatises as his Tajrīd al-iʿtiqād on theology, the Zīj-i Īlkhānī on astronomy, the Ḥall mushkilāt al-Ishārāt , his influential commentary on Avicenna's (428/1037) Kitāb al-ishārāt wal-tanbīhāt on philosophy and logic, and his Akhlāq-i Nāṣirī on ethics. The present work contains an edition of a compendium on Persian and Arabic metrics which Ṭūsī says he wrote at the request of some friends, probably at the time of his association with the Ismailis, before the Mongol invasion and the collapse of the Niẓārī state in 654/1256. It is followed by the edition of a detailed commentary on it by the Indian scholar Muḥammad Saʿdallāh Murādābādī (d. 1294/1877). Persian, interspersed with Arabic.